Psychological Condition of Individuals with a Family History of Cancer - Kusumawaty, Ira; Yunike, Yunike (International Journal Scientific and Professional, 2023)
Cancer is a non-communicable disease caused by the growth of abnormal body tissue cells, which turn into cancer cells and is the second leading cause of death in the world by 13% after cardiovascular disease. Stigma has developed in society that cancer is a terrible and incurable curse. This assumption will make the mental condition of cancer sufferers worse and can even frustrate them. This psychiatric condition makes many cancer sufferers feel hopeless and helpless, so sufferers are reluctant to find out about cancer treatment and are resigned to their condition. Chronic psychological stress in fact accelerates cell reproduction, the more differentiated cells grow old and die, the more stem cells divide to make new cells, increasing the risk of developing cancer. The purpose of this study was to identify the psychological conditions of individuals with a family history of cancer. The method used was a literature study by conducting studies on Scopus, Pubmed, and Google Scholar with the keywords cancer, individual psychology, families with cancer. This research is expected to describe the condition of individuals with a family history of cancer.